Muscle blood flow as an indicator of anaerobic threshold in young athletes - A near infrared spectroscopy study - Chroboczek, M.; Jakubowska, M.; Kujach, S.; Luszczyk, M.; Laskowski, R. (Baltic Journal of Health and Physical Activity, 2017)
Background: In this study we evaluated the effect of exercise with increasing intensity until exhaustion on muscle tissue oxygenation in children. Furthermore, we tested the hypothesis that a decrease in muscle indirect blood flow (O2Hb) predicts the anaerobic threshold determined by analysis of ventilation parameters. Material/Methods: Five, young, school-aged tennis players were engaged in this study (age 16.2 ±1.63 years, VO2max 56.7 ±2.00 ml · kg-1 · min-1). Changes in oxygenated hemoglobin (HbO2), deoxygenated hemoglobin (HHB), blood volume (tHb = HbO2 + HHB) and muscle tissue oxygenation (TOI%) in the right vastus lateralis muscle, using a near-infrared spectrometer were recorded. Results: The hemodynamic values (HHB, tHb) increased as expected depending on the exercise intensity. Therefore, NIRS data precedes the occurrence of AT determined by the analysis of ventilation parameters, which in the case of the V-slope method was achieved at 75% VO2max. Conclusions: A correlation between the parameters of muscle tissue oxygenation and ventilation parameters shows that the anaerobic threshold occurs as a result of deoxygenation of a muscle tissue.